2017
DOI: 10.18203/2394-6040.ijcmph20172868
|View full text |Cite
|
Sign up to set email alerts
|

A study of the morbidity pattern among the elderly population in Vadodara, Gujarat

Abstract: Background: Aging is an inevitable process. Old age persons are more vulnerable to physical and social problems. The objective was to study the prevalence of health problems among elderly population.Methods: A cross-sectional study was carried out on 600 old age persons living in villages of Vadodara district. Their socio-demographic profile and morbidity pattern were assessed by face to face interview. Data were analysed by epi info version 7.Results: Around 65% of study participants have musculoskeletal prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
1
2
Order By: Relevance
“…Pranay A. Jadav 8 and Shilpa Sahukaiah 3 in their studies shows prevalence of hearing problems 14.0% and 10.76% respectively which was higher than present study.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Pranay A. Jadav 8 and Shilpa Sahukaiah 3 in their studies shows prevalence of hearing problems 14.0% and 10.76% respectively which was higher than present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Janki Bartwal 5 and Nabarun Karmakar 6 in their studies shows prevalance of musculoskeletal morbidity 34.8% and 45.0% respectively which was lesser than present study. Another study conducted by Jain NC 7 shows 43.33% prevalence of arthritis (musculoskeletal morbidities) Pranay A. Jadav 8 , Vandana Verma 9 and R. Shankar 10 in their studies finds out prevalance of musculoskeletal morbidity 64.9% , 59.7% and 57.08% respectively which was lesser than present study. Various factors like geographical variations, socioeconomic class and literacy status come into play for showing higher prevalence of musculoskeletal problems in present study compared to other studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Kumar et al (2015) and GJ et al (2016) observed that arthritis was the most common morbidity, followed by hypertension, cataracts, and diabetes. According to the study findings of Jadav et al (2017), elderly individuals had the most problems with musculoskeletal disorders (64.9%), followed by depression (54.2%) and obesity (46.2%). Similar findings were also observed by Kalasker et al (2016), where the prevalence of various disorders was musculoskeletal 63.4%, gastrointestinal 19.7%, respiratory 16.2%, cardiovascular 14.8%, nervous system 9.6%, and genitourinary 6.2%.…”
Section: Discussionmentioning
confidence: 99%